Susceptibility of Aedes aegypti (Linnaeus) (Diptera: Culicidae) Immature Forms to Ivermectin - Rosa, Cassiano Sousa; Simões, Daniel A.; Ataíde, Livia M. S.; Horta, Marco A. P.; Vilela, Evaldo F. (BioAssay, 2011)
Several mosquito populations have already exhibited resistance to various insecticides, a situation that imposes many problems in vector control programs in many countries. Several studies have recently reported a decrease in the persistence of temephos, the main larvicide used to control Aedes aegypti in Brazil, suggesting that mosquito populations have acquired resistance to this organophosphate in several states. Dengue is one of the most important arthropod-borne diseases in the world and in Brazil thousands of dengue cases are notified annualy. In order to verify the effects of ivermectin, a semi-synthetic drug widely used for treatment of livestock parisitic diseases, on Aedes aegypti larvae of 3rd and 4th instar, the insects were submitted to concentrations of 1, 5 and 10 ppm of ivermectin solution during 5, 15, 10, 60 and 1440 minutes. After 24 hours of observations, mortality rates were scored. Loss of mobility, progressive paralysis and high mortality of larvae were recorded. Observations suggest that few minutes of contact with the insect is sufficient to cause intoxication. Increases in ivermectin concentration cause a progressive mortality in A. aegypti larvae. The values presented in the present study indicate that chemical treatment using ivermectin may be an alternative to the use of ivermectin in dengue control programs.